Adaptasi Sosial Dan Budaya Dalam Perkembangan Pembelajaran, Studi Kasus SMPN 12 Barru - Jamaluddin Arifin; Muhamad Saifullah; Sayawal Akhir (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
This study aims to examine the application of social and cultural adaptation in learning at SMP Negeri 12 Barru to create an inclusive and effective learning environment. The main problem raised is the challenge of students' social and cultural diversity that affects their understanding and participation in learning. The research uses a qualitative method with a descriptive approach. Data collection through observation, interviews and document analysis to explore three main focuses: the use of inclusive language styles, the integration of local cultural elements in learning materials, and classroom management strategies. The results of the study indicate that the use of simple and relevant language facilitates adaptation between teachers and students in the learning process, especially those with a strong regional language background. The integration of local culture in learning not only strengthens students' connection with the material but also increases their sense of pride in their cultural identity. Heterogeneous classroom management strategies, involving students from various backgrounds, have been shown to increase tolerance and cooperation between students, although initially they often face challenges in the form of resistance to diversity and adjustments to learning methods. The main obstacles found were limited supporting resources and the balance between local culture-based materials and the national curriculum. This study provides recommendations for stronger teacher training and policy support in implementing diversity-based learning, so that it can serve as a model for other schools with similar characteristics.